Hubungan Dukungan Tenaga Kesehatan dengan Tingkat Kecemasan Masyarakat dalam Menerima Vaksinasi COVID-19 di Kota Kupang - Hudin, Petrus Timotius Juniardi (Cendana Medical Journal, 2023)
Abstract Background : Corona Virus Disease 2019 (COVID-19) was announced by WHO as a global pandemic because of its rapid spread and impacting various countries around the world. One of the efforts made to overcome this pandemic is to carry out mass vaccinations to create herd immunity. Anxiety about the COVID-19 vaccine affects people's willingness to receive vaccinations. Health workers have a strategic role in building public trust and conveying the benefits of vaccines in order to create confidence in the community so that people are not anxious and willing to be vaccinated. Objective: To determine the relationship between the support of health workers and the level of public anxiety in receiving the COVID-19 vaccination in Kupang City. Methods: This research is an observational analytic study using cross sectional method. The sample in this study was selected by simple random sampling with a total of 289 respondents. This study was analyzed by univariate and bivariate analysis usingcorrelation test Somers'd. Results: The results of this study showed that 250 respondents (86.5%) received good support from health workers and 39 respondents (13.5%) received less support from health workers. Then 280 respondents (96.9%) did not experience anxiety disorders, 8 respondents (2.8%) had mild anxiety disorders, and 1 respondent (0.3%) had moderate anxiety disorders. The results of the bivariate test using thecorrelation test Somers'd showed p = 0.531 or p > 0.05 which showed that there was no significant relationship between the support of health workers and the level of public anxiety in receiving the COVID-19 vaccination in Kupang City. Conclusion: There is no significant relationship between the support of health workers and the level of public anxiety in receiving the COVID-19 vaccination in Kupang City. Keywords: Health Worker Support, Anxiety Level, COVID-19 Vaccine